Women’s Political Participation and Gender Equality in Early Islam: The Era of the Prophet Muhammad and the Khulafaur Rashidin - Abdul Aziz; Prio Utomo; Mohamad Syafiq (Journal of Gender and Millennium Development Studies, 2026)
Background: Women’s political roles in early Islamic history are often underrepresented, particularly during the era of the Prophet Muhammad (SAW) and the Khulafaur Rashidin. Objective: This study aims to examine women’s political roles during these periods. Method: This research employs a qualitative literature review and content analysis of historical sources. Results: The findings show that women played active political roles despite lacking formal political rights. Their participation included preaching Islam, joining the Hijrah, pledging allegiance (Bay‘ah), engaging in jihad, and supporting warfare. Several prominent female figures contributed significantly to political life. Women also faced major challenges, including persecution by the Quraysh in Makkah, physical demands during migration and conflict, and the loss of family, property, and homeland. During the Khulafaur Rashidin period, additional difficulties arose from internal conflicts among Muslims and the influence of groups such as those led by Abdullah bin Saba. Conclusion: Women held meaningful political roles despite structural limitations. Contribution: This study highlights women’s contributions and broadens perspectives on political participation in early Islam.